Exploration the therapeutic effects of sodium houttuyfonate combined with penicillin G on methicillin resistant staphylococcus aureus infected wounds - Li, Yujie; You, Shunjie; Li, Sheng; Li, Si; Jia, Aimin; Xiang, Xiaoyan; Shen, Shi; Cai, Yan (Frontiers in Pharmacology, 2025)
BackgroundMethicillin resistant Staphylococcus aureus (MRSA) is a Gram-positive bacterium that can cause local or systemic infectious diseases, and treatment for MRSA has become a major global health issue. Sodium houttuyfonate (SH) is a natural extract of Houttuynia cordata, which has antibacterial and anti-inflammatory effects. The aim of this study is to evaluate the antibacterial effect of SH combined with penicillin G (PNC) against MRSA and its potential beneficial effects in a rat model of MRSA wound infection, and to investigate its possible mechanism in combination with network pharmacology.MethodsEvaluating the antibacterial effect of drugs through in vitro antibacterial experiments. Construct a MRSA infected wound model in SD rats and determine the optimal drug ratio based on the degree of wound healing. Hematoxylin & Eosin (H&E) staining was used to determine inflammatory cell infiltration, Masson staining was used to observe collagen fiber proliferation in the wound, Elisa method was used to detect inflammatory cytokine content in retrobulbar venous blood, and network pharmacology methods were used to elucidate possible molecular mechanisms.ResultThe MIC of SH and PNC are 60–80 μg/mL and 40–70 U/mL, respectively. The FICI of the combined group is 0.375–0.5625, and the optimal drug ratio is SH20 μg/mL + PNC15u/mL. The number of central granulocytes infiltrated in the combined group was less than that in other groups, and the levels of IL-6 and TNF-α were significantly reduced. In addition, the collagen fibers in the wound were significantly increased. Thirteen target genes were predicted through network pharmacology, among which the core targets were IL1B, IL6, MMP9, IFNG, and TNF. SH and PNG have shown good binding potential with various targets in molecular docking. Among the 83 potential pathways of action, IL-17 signaling pathway is considered a key pathway for promoting wound healing.ConclusionSodium houttuyfonate combined with penicillin G can inhibit bacterial growth in MRSA infected wounds in rats, reduce neutrophil infiltration, promote collagen fiber generation in wounds, and decrease the expression levels of inflammatory factors IL-6 and TNF-α in the blood of rats after MRSA infection. It promotes wound healing through multiple targets and pathways, and preliminarily reveals the drug’s targets and molecular mechanisms.